PENGEMBANGAN MODUL KAJIAN MATEMATIKA SEKOLAH BERBASIS PROBLEM BASED LEARNING - Dwi Purnomo; Nopem Kusumaningtyas Sumitro; Dyah Ayu Sulistyaning Cipta; Dian Fitri Argarini; Yunis Sulistyorini; Sofia Sao (Universitas Insan Budi Utomo, 2024)
The aim of this research is to develop a School Mathematics Study module based on Problem Based Learning that is valid and effective. This Problem Based Learning-based module emphasizes problem solving in understanding mathematical concepts. The School Mathematics Study Module based on Problem Based Learning refers to the 4D development model, which is only limited to the Develop stage. The data collection instrument consists of a validation sheet and problem solving test questions. The trial was carried out on students of the Universitas Insan Budi Utomo Mathematics Education study program who were taking the School Mathematics Studies course. The results of data analysis show that the module fulfill the criteria for validity and effectiveness. Expert validation and module testing. From the assessment results from two experts, an average score of 3,2 was obtained, which is a very valid criterion.